DESAIN PENGEMBANGAN ENSIKLOPEDIA TUMBUHAN OBAT BERBASIS POTENSI LOKAL DI KOTA TARAKAN - Fitri Wijarini; Zulfadli Zulfadli (Universitas Lambung Mangkurat, 2018)
Abstract. This research aimed to develop of medical plant ensiclopedia based of research about medical plant research in the Tarakan City. This research used Sugiono model, consist of three stages: research, development, and research again. The results of the research and development was a draft of medical plant enciclopedia based on local potential. Keywords: Ensiclopedia, medical plant, local potential